Exploring students’ speaking anxiety at Akademi Laut Malaysia / Shamsul Rizal Mohd Rosedi...[et al.] - Mohd Rosedi, Shamsul Rizal; Ali, Nurshuhada; Mat Rom, Normaizura; Md. Sap, Mohd Asri (2018)
This paper explores the speaking anxiety of 106 first year nautical and marine engineering cadets at the Akademi Laut Malaysia (ALAM). As the English language is the language of instruction in the maritime education and training institutions, it creates inconvenience to students in coping with the language requirements and classroom instructions. The promulgation of English as the working language of the maritime industry has increased this anxiety even more. Ironically, in both classrooms and on board merchant ships, students must be able to communicate effectively especially in communicating essential information for the safety of operations. Hence, it is worthwhile to explore the possibility of speaking anxiety in both nautical and marine engineering classrooms for the benefit of industry. A quantitative survey, adapted from Horwitz’s (1986) Foreign Language Anxiety Scale (FLAS) was administered on respondents and the data collected were then analysed by SPSS version 22 for further analysis and understanding. The results of this study show that there is a significant level of speaking anxiety among the survey respondents which needs be addressed effectively.